2014
DOI: 10.1016/j.cub.2014.01.046
|View full text |Cite|
|
Sign up to set email alerts
|

Human Hippocampus Arbitrates Approach-Avoidance Conflict

Abstract: SummaryAnimal models of human anxiety often invoke a conflict between approach and avoidance [1, 2]. In these, a key behavioral assay comprises passive avoidance of potential threat and inhibition, both thought to be controlled by ventral hippocampus [2–6]. Efforts to translate these approaches to clinical contexts [7, 8] are hampered by the fact that it is not known whether humans manifest analogous approach-avoidance dispositions and, if so, whether they share a homologous neurobiological substrate [9]. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
145
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 29 publications
25
145
3
Order By: Relevance
“…Lesion and optogenetics studies have demonstrated an essential role for the ventral HPC in anxiety and fear (Kjelstrup et al, 2002; Kheirbek et al, 2013). Further, a series of well designed studies in humans demonstrated the importance of the ventral HPC in anxiety-related behaviors associated with approach–avoidance conflicts similar to the ones tested in this study (Bach et al, 2014). Although there remains a debate as to whether smaller hippocampal volume represents a premorbid or an acquired trait in PTSD, our results suggests that a structurally reduced hippocampus may predispose rats to exhibit aberrant post-traumatic stress responses.…”
Section: Discussionsupporting
confidence: 66%
“…Lesion and optogenetics studies have demonstrated an essential role for the ventral HPC in anxiety and fear (Kjelstrup et al, 2002; Kheirbek et al, 2013). Further, a series of well designed studies in humans demonstrated the importance of the ventral HPC in anxiety-related behaviors associated with approach–avoidance conflicts similar to the ones tested in this study (Bach et al, 2014). Although there remains a debate as to whether smaller hippocampal volume represents a premorbid or an acquired trait in PTSD, our results suggests that a structurally reduced hippocampus may predispose rats to exhibit aberrant post-traumatic stress responses.…”
Section: Discussionsupporting
confidence: 66%
“…Both of these studies implicated the anterior hippocampus (in addition to PFC and amygdala). Bach and colleagues (2014) additionally offered evidence that the anterior hippocampus particularly tracked level of threat and that individuals with hippocampal sclerosis are less impacted by threat (consistent with animal work described above).…”
Section: Human Paradigmssupporting
confidence: 68%
“…It has been confirmed that the hippocampus plays a role in processing exploratory conflict, and may be involved in biasing behavior away from rewarding outcomes (Bach et al, 2014; O'Neil et al, 2015; Schumacher et al, 2016). Human behavioral research with both approach-avoidance conflict and open field paradigms has supported the impact of anxiety and gender on avoidance behavior and/or thigmotaxis (Aupperle et al, 2011; Kallai et al, 2007; Walz et al, 2016), thus partially validating the use of such paradigms as preclinical animal paradigms.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Unsurprisingly, the study of such approach/avoidance conflict has a long history in experimental psychology (Miller, 1944). Across species boundaries and specific task designs, approach/avoidance conflict elicits particular behaviors (Aupperle, Sullivan, Melrose, Paulus, & Stein, 2011; Bach et al, 2014; Calhoon & Tye, 2015; Gray, 1982; Gray & McNaughton, 2000; Rodgers, Cao, Dalvi, & Holmes, 1997). This includes passive avoidance of the situation, behavioral inhibition (BI)—interruption of ongoing actions and suppression of overt approach or avoidance—and exploratory actions for risk assessment.…”
mentioning
confidence: 99%